#MeToo media and Hollywood: challenging sexual violence in film and television and the limits of media industries - Lynn, Emma, author; Marx, Nick, advisor; Diffrient, Scott, committee member; Gibson, Katie, committee member; Chatterjee, Sushmita, committee member (Colorado State University. Libraries, 2025)
Ever since bombshell news reports exposed media mogul Harvey Weinstein as a sexual predator in 2017, there has been an influx of narrative film and television texts that address the #MeToo movement—both implicitly and explicitly—in their narratives. Taken together, these texts make up a distinct cycle of film and television I term "#MeToo Media." This dissertation seeks to uncover how Hollywood comes to terms with the #MeToo movement through its relationship with the #MeToo Media Cycle. #MeToo Media both challenge and reinforce power dynamics in Hollywood. On the one hand, these texts can productively engage in #MeToo discourses and challenge sexual violence through narrative storytelling. On the other hand, #MeToo Media can be a mechanism for Hollywood to pay lip service to the #MeToo movement without confronting the larger structural issues that enabled Harvey Weinstein in the first place. I analyze how these tensions play out across industrial contexts, from mainstream Hollywood to independent cinema to streaming television. Ultimately, this dissertation argues that the transgressive potential of #MeToo Media is often limited by the regressive practices of the media industry institutions that produce, exhibit, and award them.
Keywords: film; sexual violence; television; Hollywood; #MeToo; streaming